A BRIEF OBSERVATION ON THE JUVENILE PRAWN FISHERY OF KILLAI BACKWATERS IN THE CAUVERY DELTA - Subramanian, V Thangaraj (Indian Journal of Fisheries, 2011)
The stake-net fishery has revealed that the juvenile prawns enter the backwaters in two annual waves, in July September and December-January, coinciding with moderate inflow of freshwater. P. indicus (44.4%), M. monoceros (33.7%) and M. dobsoni (15.9%) were the dominant components of the fishery. Their modal lengths were respectively 55-110 mm, 50-95 man and 35-65 mm, and the estimated monthly growth-rates for females while in the backwaters were 19.9 mm and 17.9 mm, 12.6 and for males 9.7 mm and 10.5 and 9.3 mm.